KAJIAN SASTRA BANDINGAN CERPEN GADIS KOREK API DENGAN CERPEN TERESA : PENDEKATAN PSIKOLOGI SASTRA - Naziha, Silvi Athala; Hartati, Dian (Universitas Hamzanwadi, 2022)
This research is important to do in order to determine the psychological condition that occurs in a woman as a follow-up and the violence she experienced. This study aims to describe the differences and similarities in the main female characters in the title Gadis Korek Api by Djenar Maesa Ayu with the poem Teresa by Paulina Flores. The method used in this research is descriptive analysis. The technique used in this research is reading and notetaking technique. The approach taken is using the Psychological Theory of Sigmund Freud (1923) there are three personality elements in psychoanalysis, namely the Id, Ego, and Superego. The results of the study reveal that (1) there are similarities in the two literary works, namely actions against women, (2) differences in the main female characters in the two works, as Nayla has a different ego personality from Id. Meanwhile, Claudia in Teresa's short story is more dominant in personality I than following Ego. Keywords: Comparative Literature, Psychology, Short Stories.